Psychological and Social Factors Influencing Eating Behaviors in College Athletes - Bulut, Sefa; Rostami, Mehdi; Hajji, Jamel; Boltivets, Sergii; Saadati, Nadereh; Yang, Jiantang; McDonnell, Maura; Chikwe, Chidinma; William, Erwin A. (Health Nexus, 2024)
Eating behaviors among college athletes are influenced by a complex interplay of psychological, social, and nutritional factors, which can significantly impact their health and performance. This study aims to elucidate these multifaceted influences, providing a deeper understanding of the factors that shape eating behaviors in collegiate sports environments. This qualitative study involved semi-structured interviews with 30 collegiate athletes from various sports disciplines across several universities. Theoretical saturation guided the data collection process until no new themes emerged. Data were transcribed verbatim and analyzed using NVivo software to conduct thematic analysis, focusing on identifying patterns related to psychological drivers, social influences, and nutritional knowledge. Three main themes were identified: Psychological Drivers, Social Influences, and Nutritional Knowledge. Psychological Drivers included Emotional Eating, Dietary Attitudes, and Motivation to Eat Well. Social Influences encompassed Peer Dynamics, Family Influence, Coaching Guidance, and Social Media Impact. Nutritional Knowledge was characterized by Understanding of Nutrition, Sources of Information, and Dietary Planning. Each theme and its categories were supported by specific concepts illustrating the complex and interconnected factors influencing athletes' eating behaviors. The study highlighted the significant role of psychological and social factors alongside nutritional knowledge in shaping the eating behaviors of college athletes. Interventions aimed at improving athletes' eating behaviors should consider these dimensions to effectively support athletes in managing their dietary habits in a way that promotes both optimal performance and general well-being.